How Municipalities Can Enhance Citizen Participation? – Exploring the Views of Participants and Non-Participants - Jäntti, Anni; Kurkela, Kaisa (Scandinavian Journal of Public Administration, 2021)
In this study, we scrutinise how municipalities can enhance citizen participation as arenas for local democracy. We combine the aspects of institutional structures with citizens’ expectations and viewpoints by analysing citizens’ views on the barriers to and catalysts for participation. We outline the possibilities and map the role of municipalities in enhancing citizen participation. This qualitative study utilises empirical data consisting of 160 essays written by university students. In their essays, students reflect on their roles as participants and think about possible obstacles to participation. The data is analysed using inductive qualitative content analysis. In the analysis, three categories were identified to illustrate and interpret the societal, personal and instrumental-processual factors that affect citizens’ willingness and abilities to participate at the local level. Municipalities can easily address the instrumental-processual factors, whereas affecting societal and personal factors is more difficult. The role of municipalities in enhancing citizen participation is thus restricted, yet important.